High‐Performance Near‐IR Photodetector Using Low‐Bandgap MA0.5FA0.5Pb0.5Sn0.5I3 Perovskite. (16th May 2017) - Xu, Xiaobao; Chueh, Chu‐Chen; Jing, Peifeng; Yang, Zhibin; Shi, Xueliang; Zhao, Ting; Lin, Lih Y.; Jen, Alex K.‐Y.
Abstract : Photodetectors with ultrafast response are explored using inorganic/organic hybrid perovskites. High responsivity and fast optoelectronic response are achieved due to the exceptional semiconducting properties of perovskite materials. However, most of the perovskite‐based photodetectors exploited to date are centered on Pb‐based perovskites, which only afford spectral response across the visible spectrum. This study demonstrates a high‐performance near‐IR (NIR) photodetector using a stable low‐bandgap Sn‐containing perovskite, (CH3 NH3 )0.5 (NH2 CHNH2 )0.5 Pb0.5 Sn0.5 I3 (MA0.5 FA0.5 Pb0.5 Sn0.5 I3 ), which is processed with an antioxidant additive, ascorbic acid (AA). The addition of AA effectively strengthens the stability of Sn‐containing perovskite against oxygen, thereby significantly inhibiting the leakage current. Consequently, the derived photodetector shows high responsivity with a detectivity of over 10 12 Jones ranging from 800 to 970 nm. Such low‐cost, solution processable NIR photodetectors with high performance show promising potential for future optoelectronic applications. Abstract : A high‐performance NIR photodetector derived from a stable low optical bandgap ( E g ) Sn‐containing perovskite, MA0.5 FA0.5 Pb0.5 Sn0.5 I3, is introduced. Ascorbic acid is used as an effective antioxidant additive to enhance the performance of the photodiode. Finally, a high detectivity of over 10 12 Jones between 800 and 970 nm with a high response rate is achieved.